Ultrasound assisted photocatalytic oxidative desulfurization of model diesel fuel. (2nd January 2018) - Zhao, Meng; Han, Pingfang; Lu, Xiaoping
ABSTRACT: Ultrasound assisted photocatalytic oxidation technology is an efficient and gentle technology to remove the organic sulfur from diesel. The influence parameters of catalytic oxidation phase include catalyst dosage, reaction temperature, oxidation time, hydrogen peroxide to diesel fuel ratio and time of the extraction process. Furthermore, the comparison of the results under two conditions of ultrasound irradiation and mechanical agitation are also specially examined. The obtained results indicate that under the optimal condition, ultrasound assisted oxidative desulfurization (UAOD) is more efficient for sulfur removal which the desulfurization degree can be reached 99.47%.